2002
DOI: 10.1007/s10006-002-0430-3
|View full text |Cite
|
Sign up to set email alerts
|

Erweiterte Diagnostik im Rahmen der operativen Weisheitszahnentfernung mittels digitaler Volumentomographie

Abstract: In summary, DVT is an advantageous and practical imaging technique that can be used for to extend the diagnosis in surgery on third molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 9 publications
0
5
0
5
Order By: Relevance
“…CBCT reduces radiation exposure and gives almost equivalent images compared to computed tomography [34,35,40,53,54]. CBCT is superior to conventional X-ray diagnosis in identifying root configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT reduces radiation exposure and gives almost equivalent images compared to computed tomography [34,35,40,53,54]. CBCT is superior to conventional X-ray diagnosis in identifying root configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Haney et al [31] reported that there was a 27% change in the therapy Wurzelresorptionen am seitlichen Inzisivus wird in verschiedenen Studien hingewiesen [1,17,26]. Bei reduzierter Strahlenbelastung ermöglicht die digitale Volumentomographie der CT annähernd gleichwertige Aufnahmen [34,35,40,53,54] und ist der konventionellen Röntgendiagnostik in der Erkennung von Wurzelkonfigurationen überlegen.…”
Section: Discussionunclassified
“…Die Darstellung der Fragmente und Nachbarstrukturen schnitt bei beiden Parametern mit einem Median von 2,5 nur gering schlechter ab (Abbildung 9). reasons for CBCT imaging in both specialist literature [12,24], which is why interdisciplinary consultation makes sense in individual cases prior to radiologic examination.…”
Section: Arcadis Orbic 3dunclassified
“…Their configurations vary from system to system: In addition to diagnostic imaging similar to CT, i.e., with images taken with the patient supine, there are orthopantomogram (OPT)-similar devices for sitting patients, and mobile systems developed for intraoperative examination. Initial reports in the dental literature dealt predominantly with dentoalveolar processes (impacted teeth, cysts), dental implants, or issues concerning maxillofacial surgery (fractures, paranasal sinuses, osteomyelitis) [1,7,9,10,12,15,17,23,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation